Tata Kelola Pemerintah dalam Penanggulangan Kondisi Bencana Banjir di Kawasan Permukiman Pahandut Seberang - Indra Junedi; Indrawan Permana; Theresia Susi (Universitas 17 Agustus 1945 Semarang, 2025)
This research aims to find out the Governance of the Government in Overcoming Flood Disaster Conditions in the Pahandut Seberang Settlement Kawasam. The research method used in this research is descriptive method. Data was collected through field observations. This research was conducted in Pahandut Seberang Village, Palangka Raya City, Central Kalimantan Province. Based on existing data as a research site in flood-affected areas in Pahandut Seberang Village at the location of residents in RT 02, 03, 04 and 05. The research time was carried out from the date of issuance of the research permit within a period of 3 (three) months, 1 (one) month of data collection and 2 (two) months of data analysis. Materials and tools used in research include stationery, cameras, and observation guides. The process of analysing qualitative research data is an integral part of data analysis activities such as: data reduction, data presentation & conclusion drawing/verification. The results of this study indicate that to be able to get solutions to overcome these various obstacles, namely: Flooding in Kelurahan Pahandut Seberang has a significant impact on the social and economic conditions of the community. Social impacts include damage to homes, disruption of daily activities, and health problems. Economic impacts include losses from the agriculture sector, small businesses, and loss of transport access.